Authentic leadership, happiness at work and affective commitment: An empirical study in Cape Verde. Issue 3 (13th May 2019) - Semedo, Ana Suzete; Coelho, Arnaldo; Ribeiro, Neuza
Abstract : Purpose: This study aims to investigate the relationship between perceptions of authentic leadership (AL) and affective commitment (AC) both directly and indirectly through the mediating effect of happiness at work. Design/methodology/approach: Empirical research has analyzed the data from a questionnaire administered to a sample of 543 employees belonging to various public and private organizations in Cape Verde. Structural equation modeling was used to test the model. Findings: It was found that the perceptions of AL explain employees' happiness at work. Perceptions of AL also predict AC both directly and through the mediating effect of happiness at work. Practical implications: The findings suggest that AL predicts happiness at work, which, in turn, explain employees` emotional bond to the organization. These results provide evidence that the quality of working environment created by leaders plays an important role in the extent to which employees develop a better emotional bond at work. So, the organizations, particularly in Cape Verde, should focus on training leaders with authentic characteristics. Originality/value: In addition to verifying the direct relationship between AL and AC, this study introduced the mediating effect of the happiness, providing a model that depicts the chain effect between AL, AC and happiness, integrating these concepts in a single study.